1994
DOI: 10.1515/jpme.1994.22.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of severe birth asphyxia and early prediction of neonatal neurological outcome in term asphyxiated newborns

Abstract: Ten indicators available during the first two hours of life, such as clinical criteria of neonatal distress and postnatal arterial blood gases, were compared with the neonatal neurological course in sixty full term newborns with significant birth asphyxia in order to test their value for the diagnosis and the short-term prognosis of severe birth asphyxia. Birth asphyxia was defined as severe when it was followed by symptoms of moderate or severe post-asphyxial encephalopathy. We calculated a sensitivity lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Technology based tests such as the electroencephalogram and magnetic resonance imaging have high predictive value but they are not always available in standard neonatal intensive care units. Also, clinical predictors of proven reliability such as delayed onset of breathing (9,10), chest compression and seizures are not always present in every asphyxiated infant. Moreover, the absence of these risk factors does not preclude an adverse neurological outcome.…”
mentioning
confidence: 99%
“…Technology based tests such as the electroencephalogram and magnetic resonance imaging have high predictive value but they are not always available in standard neonatal intensive care units. Also, clinical predictors of proven reliability such as delayed onset of breathing (9,10), chest compression and seizures are not always present in every asphyxiated infant. Moreover, the absence of these risk factors does not preclude an adverse neurological outcome.…”
mentioning
confidence: 99%
“…In full-term neonates the scoring systems described by Portman et al [10], Perlman or Wayenberg et al [15] are used for an early selection of neonates with a poor outcome. The score by Portman et al [10] is based on fetal heart rate patterns, 5-min Apgar score and base deficit within 60 min after birth in full-term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…For assessing the score by Wayenberg et al [15] it is necessary to perform a neurological examination at 30 min after birth. This is often impossible in ventilated neonates undergoing intensive care treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient we assigned an early neurological score (ENS) at 30 min of life [29] graded from 0 to 6 according to the level of consciousness (normal/hyperalertness ¼ 2, lethargy ¼ 1, stupor ¼ 0), the respiration pattern (regular ¼ 2, irregular ¼ 1, absent ¼ 0) and the primitive Moro and grasping reflexes (normal/increased ¼ 2, depressed ¼ 1, absent ¼ 0). We calculated the logistic score (LS) as a function of arterial base deficit at 30 min of life (BD30) and ENS: LS ¼ (0.33 6 BD30) -ENS, as previously described [14].…”
Section: Indicatorsmentioning
confidence: 99%
“…Scoring systems [22,23], cerebral function monitoring [24][25][26], and urinary lactate/creatinine ratio [27,28] are very useful, but have been validated only after 4-6 h of life. In a cohort of symptomatic term infants, we found neurological status and postnatal arterial base deficit both determined at 30 min of life to be the most discriminating indicators of the neonatal neurological evolution [29]. Thereafter, we demonstrated that a combination of a single neurological score and postnatal arterial base deficit at 30 min of life was a sensitive and predictive indicator of the occurrence of moderate to severe NE following perinatal asphyxia [14].…”
Section: Introductionmentioning
confidence: 99%